PENERAPAN SISTEM FULL DAY SCHOOL (STUDI SOSIOLOGI PENDIDIKAN DI SMA ISLAM AS-SHOFA PEKANBARU) - Septianawati, Mira Pefti; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at As-Shofa Islamic High School Pekanbaru with the aim of finding the application of a full day school system at As-Shofa Pekanbaru Islamic High School and its impact on students, teachers and parents. Some questions in this study are (1) How is the implementation of a full day school system in As-Shofa Islamic High School? (2) What is the impact of implementing a full-day school for students, teachers, and parents ?, The title of this study is "Implementation of a Full Day School System (Sociological Study of Education in As-Shofa Pekanbaru Islamic High School)". This research was conducted to study the application of a full day school system at As-Shofa Islamic High School Pekanbaru. To find out how to implement a full-day school for students, teachers, and parents. Subjects in this study were students who attended As-Shofa Islamic High School in Pekanbaru as many as 4 people, teachers at As-Shofa Islamic High School Pekanbaru numbered 2 people, and also as many as 4 parents. In conducting data collection using observation, interviews, and documentation. To analyze the problems in this study, qualitative analysis is used and will be described descriptively in conducting the author. After conducting the research, the results of the study discussed the implementation of a full-day school system at As-Shofa Pekanbaru Islamic High School that was agreed and efficiently in accordance with the regulations implemented by the government, namely Republic of Indonesia Minister of Education and Culture Regulation No. 23 of 2017 concerning school. While a full evaluation of a day's school for students The benefit is a learning process that becomes more because learning takes longer, while the disadvantages are that students become increased due to a busy schedule. For the teacher, the benefits of the teacher will be more professional because they are always required to deliver the material well, while the loss of the teacher's workload will increase. For parents, the benefit is to divert parents to children less, while the disadvantage is that time is denied by their children being shorter.Keywords: full day school, impact, application.